High-risk stress fractures: diagnosis and management - McInnis, K. C.; Ramey, L. N. (PM&R, 2016)
Stress fractures are common overuse injuries in athletes. They occur during periods of increased training without adequate rest, disrupting normal bone reparative mechanisms. There are a host of intrinsic and extrinsic factors, including biochemical and biomechanical, that put athletes at risk. In most stress fractures, the diagnosis is primarily clinical, with imaging indicated at times, and management focused on symptom-free relative rest with advancement of activity as tolerated. Overall, stress fractures in athletes have an excellent prognosis for return to sport, with little risk of complication. There is a subset of injuries that have a greater risk of fracture progression, delayed healing, and nonunion and are generally more challenging to treat with nonoperative care. Specific locations of high-risk stress fracture include the femoral neck (tension side), patella, anterior tibia, medial malleolus, talus, tarsal navicular, proximal fifth metatarsal, and great toe sesamoids. These sites share a characteristic region of high tensile load and low blood flow. High-risk stress fractures require a more aggressive approach to evaluation, with imaging often necessary, to confirm early and accurate diagnosis and initiate immediate treatment. Treatment consists of nonweight-bearing immobilization, often with a prolonged period away from sport, and a more methodic and careful reintroduction to athletic activity. These stress fractures may require surgical intervention. A high index of suspicion is essential to avoid delayed diagnosis and optimize outcomes in this subset of stress fractures.